Poverty in Indonesia: A Comparison Between the World Bank Poverty Line and the Indonesian Government Poverty Line - Agatha Helena Deze; Thomas Ola Langoday; Marius Masri (PT FORMOSA CENDEKIA GLOBAL, 2026)
Poverty remains a major development challenge in Indonesia. This article aims to compare poverty measurement in Indonesia based on the poverty line established by the World Bank and the one used by the Indonesian government, in this case the Central Statistics Agency (Badan Pusat Statistik – BPS). This study is a descriptive-comparative quantitative research. These discrepancies reflect variations in the methodology used by BPS compared with the methodology adopted by the World Bank. Additionally, there are differences in assessing sensitivity to minimum living standards in Indonesia and globally. The findings of this study highlight the importance of harmonizing poverty measurement and its implications for more inclusive and well-targeted social protection policies.